Citywide Inclusive Sanitation: A Public Service Approach for Reaching the Urban Sanitation SDGs - Schrecongost, Alyse; Pedi, Danielle; Rosenboom, Jan Willem; Shrestha, Roshan; Ban, Radu (Frontiers in Environmental Science, 2020)
This policy brief sets out key concepts, principles and practical implications for the Citywide Inclusive Sanitation (CWIS) approach. Rapid urbanization, aging infrastructure, and climate change are exacerbating a sanitation crisis. The focus of most urban sanitation interventions remains incremental expansion of centralized sewer infrastructure; little attention is paid to reaching the poor, long-term service provision, financial viability, or the public system functions required to achieve those outcomes. Meeting SDG targets requires a radical rethink of the urban sanitation sub-sector. Citywide Inclusive Sanitation offers this. This paper presents a public services framework, set out by the Gates Foundation, for pursuing equitable, safe and sustained service outcomes, at city scale. It reviews the genesis and evolution of the CWIS Framework and shares key principles and policy implications.